Sessiia verkhovnogo soveta Rossiiskoi Federatsii . Sessiia verkhovnogo soveta Rossiiskoi Federatsii . Session of the Supreme Soviet of the Russian Federation . Сессия Верховного Совета Российской Федерации - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Program discussing the draft law on the privatization of housing and communal services. Featured in the program: Khasbulatov, Ruslan Imranovich (Chairman of the Supreme Soviet of the Russian Federation) Обсуждение проекта закона о приватизации жилищно-коммунального хозяйства. В программе участвуют: Хасбулатов, Руслан Имранович (Председатель Верховного Совета Российской Федерации)